Resistant Starch a New Weapon against Disease Fighting of Potato Eater: A focused review - Chakraborty, Rajesh (Asian Journal of Pharmaceutics (AJP), 2016)
Conventionally, the potato eater of Bangladesh intakes the normal starch from their potato foodstuffs. However, the phenomenon, â€œresistant starch (RS)â€ is the most crucial for our health and body against diseases. From these perspectives, this study was conducted to evaluate the most precise characteristics of RS from which we can get more and more benefits to lead a better life from potato. The interest of RS of potato varied from men to men and the intensity of taking the RS depends on the amount of starch intake. It can regulate the insulin and blood sugar. The cooking procedures and the cooling techniques may vary the amount of starch of potato which is indigestible in nature. After cooking, the cooling increases the percent of RS of potato. Finally, it may be said that the RS could change our health into a good sign as healthy men.